2014
DOI: 10.1002/pbc.25236
|View full text |Cite
|
Sign up to set email alerts
|

Topical analgesia treats pain and decreases propofol use during lumbar punctures in a randomized pediatric leukemia trial

Abstract: This study demonstrated that the combination of EMLA cream with propofol is beneficial. Topical analgesics are at the discretion of the oncologist, allowing us to advocate for patients by providing safe and efficacious pain management for lumbar punctures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…The outcome of this study revealed that the application effectively anesthetized the teeth and gingiva, so the dental work was performed with comfort. A study 19 demonstrated that the combination of EMLA cream with propofol is beneficial and providing safe and effective pain management for lumbar punctures.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of this study revealed that the application effectively anesthetized the teeth and gingiva, so the dental work was performed with comfort. A study 19 demonstrated that the combination of EMLA cream with propofol is beneficial and providing safe and effective pain management for lumbar punctures.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation for the children in this study was performed by intravenous administration of Propofol in available central iv access. EMLA (eutectic mixture of local anesthetics) was used as a pain reliever (Whitlow et al, 2015). The sedation was administrated in the presence of the child's parent, who left the room when the child was no longer awake.…”
Section: The Procedures -Sedation For Intrathecal Chemotherapymentioning
confidence: 99%
“…Numerous psychological interventions, such as cognitive-behavioural strategies, hypnosis, virtual reality and music therapy, have thus been introduced to reduce children's stress and anxiety (Flowers and Birnie, 2015;Nguyen et al, 2010;Nilsson et al, 2009;Richardsson et al, 2006). Most interventions to promote children's well-being during treatment with intrathecal chemotherapy requiring lumbar puncture are pharmacological (Whitlow et al, 2015). The procedure for receiving sedation for intrathecal chemotherapy does, however, create a particularly difficult situation for the child.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of any sign of local erythema, swelling, and allergic reaction was verified, and the skin was wiped dry and sterilized according to standard procedures prior to performing the LP. Additional intermittent bolus doses of 0.5 to 1 mg/kg of propofol were administered when needed to avoid movement of the patient related to the procedure . The patients had continuous monitoring of their electrocardiogram, respiratory rate, capnography, pulse oximetry, and noninvasive measurement of blood pressure every 3 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Propofol is a general anesthetic drug that is administered as a single drug or in combination with systemic or local analgesics for procedural sedation . Fentanyl and alfentanil are the commonly used systemic analgesics, and subcutaneous 1% lidocaine injection or eutectic mixture of lidocaine and prilocaine cream (EMLA cream) application are the commonly used local analgesics for these procedures . Inclusion of systemic or local analgesic to propofol has been demonstrated to improve pain control with fewer adverse effects .…”
Section: Introductionmentioning
confidence: 99%